Transesthetics of waste (Critique of pure sensation) - Duque, Félix (Estudios de Filosofía, 1997)
The article aims to clarify the meaning of art in last decades by proposing a critique of pure sensation of traditional aesthetics. The West tradition has over looked for a long time the ’residual’ component of human life because it fears to acknowledge the finite and dependent character of existence, as well as the difficulty we find in trying to turn this component into an object of analysis. This attitude is comprehensible, in a sense, because the ’residual’ can not be reduced to form and concept. During last years (from Duchamp’s aesthetical ecology), art has been attentive to the ’residual’. The author calls its highest concern ’transaesthetics of residuals’ and underlines the fact that in that level the fluid and decaying hove taken the place of the ’permanent ’. As consequences of this movement, life and death are seen as dialectically related and, second following an ’aesthetics of transgression ’, it has been possible to talk about an aesthetics without metaphysics, surpassing nausea and melancholy by means of pity.